SIFAT KIMIA BIOCHAR PELEPAH KELAPA SAWIT DARI NEGERI LAMA SEBERANG, KABUPATEN LABUHANBATU - Reynaldi, Bayu; Septyani, Ika Ayu Putri; Walida, Hilwa; Rizal, Khairul (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Oil palm fronds are waste products of oil palm plantations that are not utilized, yet oil palm fronds can be converted to biochar to improve soil fertility. This study aimed to analyze the chemical properties of the biochar generated from oil palm fronds. A pot experiment was conducted in Negeri Lama Seberang Village, Labuhanbatu District, Rantauprapat. The biochar formulation consisted of two formulations, i.e., A = pure biochar  (biochar in its original form) and B = granule biochar (biochar + tapioca flour). Each biochar form was repeated five times to obtain ten samples. The results of biochar laboratory analysis were continued with statistical tests based on the dependent t-test at the 5% level using Microsoft Excel. The results showed that biochar granules had chemical characteristics such as organic C of 32.78%, N of 2.39%, P of  0.18, K of 0.75%, and pH of 8.07. These values showed that granule biochar has better chemical characteristics than pure biochar.